Análisis Aerodinámico de la Aeronave usb Aero Mediante Dinámica de Fluidos Computacional - Sanchez Ocampo, Juan Gabriel; Tamayo Andrade, Jordy Francisco; Lopez Aragon, Sergio Andres; Cerpa Bernal, Rafael Mauricio (TECCIENCIA, 2020)
The present research study presents the results of the aerody- namic analysis of a USB AERO aircraft using computational ﬂuid dynamics (CFD) in operational conditions of cruise ﬂight at an angle of attack of 3.5 degrees. The ANSYS FLUENT computational tool was used, with which the lift, drag and longitudinal momentum coeﬃcients were determined. Addi- tionally, the aircraft was analyzed at diﬀerent angles of attack in order to determine aerodynamic characteristics such as the highest lift coeﬃcient and the loss angle, in addition to establishing the maximum aerodynamic eﬃciency.